Force Variability during Dexterous Manipulation in Individuals with Mild to Moderate Parkinson’s Disease - Ko, Na-hyeon; Laine, Christopher M.; Fisher, Beth E.; Valero-Cuevas, Francisco J. (Frontiers in Aging Neuroscience, 2015)
Parkinson’s disease (PD) is a progressive neurodegenerative disease affecting about 1-2% of the population over the age of 65. Individuals with PD experience gradual deterioration of dexterous manipulation for activities of daily living, however, current clinical evaluations are mostly subjective and do not quantify changes in dynamic control of fingertip force that is critical for manual dexterity. Thus, there is a need to develop clinical measures to quantify those changes with aging and disease progression. We investigated the dynamic control of fingertip forces in both hands of 20 individuals with PD (69.0 ± 7.4 years) using the Strength-Dexterity test. The test requires low forces (< 3N) to compress a compliant and slender spring prone to buckling. A maximal level of sustained compression is informative of the greatest instability the person can control, and thus is indicative of the integrity of the neuromuscular system for dexterous manipulation. Miniature sensors recorded fingertip force (F) during maximal sustained compressions. The force variability during sustained compression was quantified in two frequency bands: low (<4 Hz, F_LF) and high (4-12 Hz, F_HF). F_LF characterizes variability in voluntary fluctuations while F_HF characterizes variability in involuntary fluctuations including tremor. The more-affected hand exhibited significantly lower F and lower F_LF than those in the less-affected hand. The more-affected hand showed significant negative correlations between F_LF and the UPDRS motor scores for both total and hand-only, suggesting that greater force variability in the voluntary range was associated with less clinical motor impairment. We conclude the nature of force variability in the voluntary range during this dynamic and dexterous task may be a biomarker of greater motor capability/flexibility/adaptability in PD. This approach may provide a more quantitative clinical assessment of changes of sensorimotor control in individuals with PD.